Current-carrying contact character and wear behavior of an elastic ring at different rolling speeds. (January 2022) - Chen, Tianhua; Song, Chenfei; Zhang, Yanyan; Niu, Kai; Liu, Zili; Wang, Li; Sun, Chao; Li, Mengjia; Zhang, Yongzhen
Highlights: The damage degree of the rolling ring surface increases with the rotation speed. The current can promote fatigue wear of the rolling ring. The tribological and electrical properties can be considered simultaneously by optimizing the contact area. Abstract: Novel current-carrying contact pairs were designed in this study, consisting of an inner raceway, outer raceway, and elastic ring. The effect of rotation speed on the current-carrying tribological properties was investigated using a rolling tribometer. As the rotation speed increased from 240 r/min to 600 r/min, the total friction force in the steady-state period increased from 3.8 N to 7.6 N, and the contact resistance decreased from 0.52 Ω to 0.34 Ω. Scanning electron microscopy and optical microscopy revealed that high rotation speeds and the presence of a current promoted surface fatigue and the generation of cracks. The X-ray photoelectron spectroscopy results indicated that more nascent metals were exposed on the rolling surface at higher speeds, which is beneficial for the electric contact. Compared with previous rigid rolling pairs, the weight of the elastic ring was significantly reduced, and no arcing occurred at high rotation speeds. These results can provide a reference for the design of new high-speed rotating conductive joints.